A theoretical strategy of pure carbon materials for lightweight and excellent absorption performance. (15th April 2021) - Yan, Xu; Huang, Xiaoxiao; Chen, Yanting; Liu, Yuhao; Xia, Long; Zhang, Tao; Lin, Haiyan; Jia, Dechang; Zhong, Bo; Wen, Guangwu; Zhou, Yu
Abstract: Developing the pure carbon materials with ultra-light and excellent electromagnetic wave absorption (EWA) performance that aims to solve signal interference or electromagnetic pollution is highly desirable. However, there still remains a huge challenge that whether the pure carbon materials with excellent conductivity can be used as EWA alone and how the performance can be optimized. Keeping the high conductivity and adjusting the relaxation intensity ( Δε ) at the same time are theoretically found to be the effective way to improve the attenuation of electromagnetic wave and obtain better impedance matching. Herein, the key relationship between Δε and EWA property is proved by theoretical calculation. As the experimental design, the pure carbon absorber, CMF (carbonized melamine foam, the density of 4.34 mg cm −3 ), which holds highly conductivity and appropriate Δε, exhibits a strong absorption (−57.3 dB) and a wide effective absorption band of 8.32 GHz. It is verified when carbon material possesses excellent conductivity, it is easy to steer the optimized design of Δε toward improving the impedance matching. Meanwhile, the strategy developed here paves a new way for the design of high conductivity and ultralight EWA materials for the practical applications. Graphical abstract: Image 1 Highlights: A basis theoretical strategy of carbon absorber has been fully developed. The theoretical strategy contain key factors: relaxation intensity and conductivity. Theoretical study, experiments and simulation were explored for high performance. When relaxation intensity is optimized to 5, broadband and ultralight are achieved. Absorber (4.34  mg cm −3 ) exhibits the strong (−57.3 dB) and wide (8.32 GHz) absorption.